Seasonal variations in physiological response and heat tolerance indices of Sahiwal, HF x Sahwial crossbred and Hill (Badri) Cattle under farm conditions of Uttarakhand - Pattoo, Raoof Ahmad; Singh, Devi Vrath; Dar, Prawaz Ahmad; Shah, Anees Ahmad; Adil, Sheikh; Nazir, Suheela (Indian Journal of Dairy Science, 2019)
Present investigation was conducted on Sahiwal, crossbred (Sahiwal x Holstein Friesian) and Hill (Badri) cattle to study the effect of season on physiological response and heat tolerance indices under farm condition in foot hills of Uttarakhand. Physiological responses of eighteen primiparous lactating cows (four in each group) were recorded daily in morning (9:00 am) and evening (3:00 pm) for 20 days in summer, rainy and winter season. Heat tolerance indices like Temperature humidity index, Iberia heat tolerance coefficient, Benezara coefficient of adaptability and Dairy search index were calculated. There was a significant (P≤0.05) difference between mean morning and evening rectal temperature (RT), respiration (RR) and pulse rate (PR) between indigenous and crossbred cows during summer and rainy season. Also significant (P≤0.05) difference was found between winter vs. summer/ rainy season with respect to morning and evening RT, RR and PR in all the groups. Crossbred cows had RT, RR and PR than indigenous counterparts in all the season. In winter all physiological parameters were significantly (P≤0.05) lower than summer/ rainy season in all the groups. Heat tolerance indices indicated that Sahiwal cows were more heat resistant than Hill (Badri) cows and crossbred cows, the least heat resistant during summer and rainy season. Moreover, during winter season none of the groups were under climatic stress. Study indicated that indigenous breeds were more adaptive to the stressful climatic condition in foot hills of Uttarakhand.